Role of Moderate Hypothermia and Antegrade Cerebral Perfusion during Repair of Type A Aortic Dissection - Stamou, Sotiris C.; McHugh, Michael A.; Conway, Brian D.; Nores, Marcos (International Journal of Angiology, 2018)
The goal of this study was to compare early postoperative outcomes and actuarial survival between patients who underwent repair of acute type A aortic dissection with deep or moderate hypothermia.A total of 132 consecutive patients from a single academic medical center underwent repair of acute type A aortic dissection between January 2000 and June 2014. Of those, 105 patients were repaired under deep hypothermia (< 24 C°), while 27 patients were repaired under moderate hypothermia (≥24 C°). Median ages were 62 years (range: 27–86) and 59 years (range: 35–83) for patients repaired under deep hypothermia compared with patients repaired under moderate hypothermia, respectively (p = 0.451). Major morbidity, operative mortality, and 10-year actuarial survival were compared between groups.Operative mortality was 17.1 and 7.4% in the deep and moderate hypothermia groups, respectively (p = 0.208). Incidence of permanent stroke was 12.4% in the deep hypothermic circulatory arrest group and 0% in the moderate hypothermia group (p = 0.054). Actuarial 5- and 10-year survival demonstrated a trend for lower long-term mortality with moderate hypothermia compared with deep hypothermia (69% 5-year and 54% 10-year for deep hypothermia vs. 79% 5-year and 10-year for moderate hypothermia, log-rank p = 0.161).Moderate hypothermia is a safe and efficient alternative to deep hypothermia and may have protective benefits. Stroke rate was lower with moderate hypothermia.
Keywords: aortic dissection; hypothermia; outcomes; mortality; morbidity; renal failure; cardiac surgery